An Instrument for Classifying Organizations - Oliver, John E. (Academy of Management Journal, 1982)
The objective of this research was to develop an instrument to classify organizations and subunits of organizations using Miner's (1979) four limited domain theories. Analysis of 100 items was conducted to select those that best discriminated among domains. The four scales developed vary significantly across domains and organizations, as hypothesized.